Is administrative-educational Information system of Institute computer technologies - Жуков, І. А.; Клименко, І. А.; Кравець, І. М. (Problems of Informatization and Control, 2007)
It is devoted to maintenance of information support of administrative and educational process in Institute of computer technologies. By authors of clause it is developed is administrative- educational formation system which assists increase of efficiency of managerial processes «a higher ed^Honal institution, allows to receive